The Gut Dysmotility Questionnaire for Parkinson's disease: Insights into development and pretest studies - Raeder, Vanessa; Batzu, Lucia; Untucht, Robert; Fehre, Annekathrin; Rizos, Alexandra; Leta, Valentina; Schmelz, Renate; Hampe, Jochen; Bostantjopoulou, Sevasti; Katsarou, Zoe; Storch, Alexander; Reichmann, Heinz; et al. (Frontiers in Neurology, 2023)
Objective Up to 48% of patients with Parkinson's disease (PD) present symptoms of gastrointestinal dysfunction, particularly constipation. Furthermore, gastrointestinal tract (GIT) related NMS appear at all stages of PD, can be prodromal by many years and have relevant impact on quality of life. There is a lack of GIT focused validated tools specific to PD to assess their occurrence, progress and response to treatment. The aim of this study was to develop and to evaluate a novel, disease- and symptom-specific, self-completed questionnaire, titled Gut Dysmotility Questionnaire (GDQ), for screening and monitoring of gastrointestinal dysmotility of the lower GIT in PD. Methods In phase 1, a systematic literature review and multidisciplinary expert discussions were conducted. In phase 2, cognitive pretest studies comprising standard pretests, interviews and evaluation questionnaires were performed in patients with PD (n=21), age- and sex-matched healthy controls (HC, n=30), and neurologists (n=11). Incorporating these results, a second round of cognitive pretests was performed investigating further patients with PD (n=10), age- and sex-matched HC (n=10) and neurologists (n=5). The questionnaire was adapted resulting in the final GDQ, which underwent cross-cultural adaptation to English language. Results We report significantly higher GDQ total scores and higher scores in five out of eight domains indicating a higher prevalence of gastrointestinal dysmotility in patients with PD than in HC (p<0.05). Cognitive pretesting improved the preliminary GDQ, so that the final GDQ was rated as relevant (100%/100%), comprehensive (100%/90%), easy to understand concerning questions and answer options (100%/90%) and of appropriate length (80%/100%) by neurologists / patients with PD, respectively. The GDQ demonstrated excellent internal consistency (Cronbach`s alpha 0.94). Evidence for good construct validity is given by moderate to high correlations of the GDQ total score and its domains by intercorrelations (rs=0.67–0.91; p<0.001) and with validated general NMS measures as well as with specific items that assess gastrointestinal symptoms. Interpretation The GDQ is a novel, easy and quick 18-item self-assessment questionnaire to screen for and monitor gastrointestinal dysmotility with focus on constipation in patients with PD. It has shown high acceptance and efficacy as well as good construct validity in cognitive pretests.